2007
DOI: 10.1186/1743-422x-4-11
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomic analysis of the family Iridoviridae: re-annotating and defining the core set of iridovirus genes

Abstract: Background: Members of the family Iridoviridae can cause severe diseases resulting in significant economic and environmental losses. Very little is known about how iridoviruses cause disease in their host. In the present study, we describe the re-analysis of the Iridoviridae family of complex DNA viruses using a variety of comparative genomic tools to yield a greater consensus among the annotated sequences of its members.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
93
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(95 citation statements)
references
References 30 publications
2
93
0
Order By: Relevance
“…The elevated frequency of genomic rearrangements among them appears to be a common feature of other vertebrate iridoviruses (23,35) and is different from the extensive conservation of a central genome core in the related double-stranded DNA (dsDNA) Poxviridae family, which is probably related to their different replicative mechanisms. This result, together with the elevated branch length observed among the three LCDV viruses in our phylogenetic analyses, might reflect that the lymphocystiviruses have evolved over an extended time period in heterogeneous host species and locations.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The elevated frequency of genomic rearrangements among them appears to be a common feature of other vertebrate iridoviruses (23,35) and is different from the extensive conservation of a central genome core in the related double-stranded DNA (dsDNA) Poxviridae family, which is probably related to their different replicative mechanisms. This result, together with the elevated branch length observed among the three LCDV viruses in our phylogenetic analyses, might reflect that the lymphocystiviruses have evolved over an extended time period in heterogeneous host species and locations.…”
Section: Discussionmentioning
confidence: 87%
“…The LCDV-Sa genome contains 183 putative ORFs, including orthologues of all 26 conserved iridovirus core genes (23). To assess the phylogenetic position of LCDV-Sa, we used the concatenated sequence of proteins encoded by the 26 core genes to calculate maximum-likelihood trees, including representatives of all groups of vertebrate iridoviruses.…”
Section: Resultsmentioning
confidence: 99%
“…To date, 12 genome sequences of iridoviruses including at least one from each genus have been completely sequenced and analysed [2,[4][5][6][7][8][9][10][11][12][13][14]. These analyses show that iridoviruses encode a number of cellular protein homologues that may be mostly involved in nucleic acid metabolism, such as ribonucleotide reductase (RR), thymidylate synthase (TS), deoxyuridine triphosphatase (DUT), and purine nucleoside phosphorylase (PNP) [15]. The presence of the cellular homologue genes may be of significant advantage for iridoviruses that independently replicate in the cytoplasm of the host cell [16].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that viral TKs are responsible for virus-efficient replication in some specific cell type, virus virulence, pathogenesis and reactivation from latency [20,28]. As for the iridoviruses, TK is conserved within the genome sequences of all the sequenced members in the family Iridoviridae and belongs to the core genes of iridoviruses [15]. Furthermore, TK activity has also been shown in Bohle iridovirus [23].…”
Section: Introductionmentioning
confidence: 99%
“…To date, the genomes of twelve iridoviruses, including FV3, have been completely sequenced [8,9], and 26 core genes have been predicted to exist in all iridoviruses [10]. One of these is a gene belonging to ERV1 (essential for respiration and viability) family.…”
Section: Introductionmentioning
confidence: 99%